Intra-Articular Injection of Alginate-Microencapsulated Adipose Tissue-Derived Mesenchymal Stem Cells for the Treatment of Osteoarthritis in Rabbits - Seongjae Choi; Jun-Hyung Kim; Jeongho Ha; Bo-Ing Jeong; Yun Chan Jung; Geun-Shik Lee; Heung-Myong Woo; Byung-Jae Kang (Hindawi Limited, 2018)
We investigated the effects of intra-articular injections of alginate-microencapsulated adipose tissue-derived mesenchymal stem cells (ASCs) during osteoarthritis (OA) development in a rabbit model of anterior cruciate ligament transection (ACLT). We induced OA in mature New Zealand white rabbits by bilateral ACLT. Stifle joints were categorised into four groups according to intra-articular injection materials. Alginate microbeads and microencapsulated ASCs were prepared using the vibrational nozzle technology. Two weeks after ACLT, the rabbits received three consecutive weekly intra-articular injections of 0.9% NaCl, alginate microbeads, ASCs, or microencapsulated ASCs, into each joint. Nine weeks after ACLT, we euthanised the rabbits and collected bilateral femoral condyles for macroscopic, histological, and immunohistochemical analyses. Macroscopic evaluation using the modified OA Research Society International (OARSI) score and total cartilage damage score showed that cartilage degradation on the femoral condyle was relatively low in the microencapsulated-ASC group. Histological analysis of the lateral femoral condyles indicated that microencapsulated ASCs had significant chondroprotective effects. Immunohistochemically, the expression of MMP-13 after the articular cartilage damage was relatively low in the microencapsulated-ASC-treated stifle joints. During the development of experimental OA, as compared to ASCs alone, intra-articular injection of microencapsulated ASCs significantly decreased the progression and extent of OA.